2016
DOI: 10.1021/acs.jafc.5b06043
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol as Selective Human MAO-A Inhibitor: Analytical Detection in Calabrian Red Wines, Biological and Molecular Modeling Studies

Abstract: The purpose of this work was to determine the kaempferol content in three red wines of Calabria, a southern Italian region with a great number of certified food products. Considering that wine cultivar, climate, and soil influence the qualitative and quantitative composition in flavonoids of Vitis vinifera L. berries, the three analyzed samples were taken from the 2013 vintage. Moreover, the Gaglioppo samples, with assigned Controlled Origin Denomination (DOC), were also investigated in the production of years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…It has been proved to be a potent MAOA and MAOB inhibitor, antioxidant, and presents neuroprotective effect in the mouse model [34,35]. In spite of that, a more recent study showed that kaempferol acts as a selective inhibitor of human MAOA which is consistent with our study [36]. Vanillic acid is a phenolic acid with formula C 8 H 8 O 4 , found in some forms of vanilla and many other plant extracts.…”
Section: Discussionsupporting
confidence: 91%
“…It has been proved to be a potent MAOA and MAOB inhibitor, antioxidant, and presents neuroprotective effect in the mouse model [34,35]. In spite of that, a more recent study showed that kaempferol acts as a selective inhibitor of human MAOA which is consistent with our study [36]. Vanillic acid is a phenolic acid with formula C 8 H 8 O 4 , found in some forms of vanilla and many other plant extracts.…”
Section: Discussionsupporting
confidence: 91%
“…In the nutraceutical field, computational techniques have been successfully used for the prediction of ligand-target binding affinity and to better understand the molecular basis of the biological responses. In silico studies also provide additional insight into the possible mechanism of action and binding mode of active compounds against metabolic key enzymes 82 .…”
Section: Resultsmentioning
confidence: 99%
“…Except that, kaempferol was reported can selectively inhibit human monoamine oxidases-A (MAO-A) in brain mitochondrial. The role of MAOs is to catalyze the a-carbon two-electron oxidation of amine substrates in the peripheral tissues and brain (Gidaro et al, 2016). So far, there are still lack of reports about the neuroprotective effect and possible mechanisms of kaempferol on I/R in vivo.…”
Section: Introductionmentioning
confidence: 99%